The need for cost professionals in the apparel and utility wholesale industries in the cities of Cacoal-RO and Pimenta Bueno-RO (Research, Society and Development, 2021)
The constant changes that affect the economic scenario, whether due to the emergence of new ways of providing services or the exponential growth of technological tools, demand increasingly greater adaptive capacities from entrepreneurs, large and small. Regardless of the administrative activity performed, knowing how to position yourself in the face of new market trends is, more than ever, an indispensable requirement for the success of projects, and it is in this context that the role played by the cost professional is extremely necessary. That said, this research aimed to collect substantial information about the work carried out by this professional in clothing industries and wholesale utilities in the cities of Cacoal and Pimenta Bueno, both located in the state of Rondônia. Despite the fact that many of the organizations that participated in the survey are micro-enterprises and still do not have the necessary conditions to maintain a cost professional in their staff - although the possibility of partnerships in order to obtain this was highlighted. type of consultancy – it was found that the provision of this service represents a significant portion of the success of organizations that adopt it. As for the methodology, semi-structured interviews were carried out through carefully organized forms from the perspective of a qualitative approach, in addition to the use of exploratory and descriptive procedures. Such research tools allowed the achievement of the objective stipulated for the research, concluding that the cost professional generates more alternative strategies for managers, resulting in greater advantages over competition in the market.